Management of Acute Hypercapnic Respiratory Failure (AHRF) in Patients with Obesity Hypoventilation Syndrome (OHS) in the Intensive Care Unit (ICU) - Ningsih, Diana Fitria; Indriasari, Indriasari (CoinReads Media Prima, 2025)
Introduction: Acute hypercapnic respiratory failure (AHRF) in patients with obesity hypoventilation syndrome (OHS) presents significant challenges in the intensive care unit (ICU), particularly when complicated by comorbidities such as community-acquired pneumonia and heart failure. Effective management requires a tailored approach addressing altered lung mechanics, infection control, and fluid balance. This case report highlights the multidisciplinary management of AHRF in a complex clinical scenario. Case Description: A 35-year-old female with OHS presented with progressive dyspnea for one month, worsening over the last two days. Initial assessment revealed type II respiratory failure with a pCO2 of 89 mmHg. Management included intubation and mechanical ventilation, initially with pressure control-assist control (PC-AC) mode, gradually transitioned to pressure support ventilation (PSV). Empirical antibiotics were administered, later adjusted based on sputum culture results. Fluid management involved furosemide to address concurrent heart failure. Adequate positive end-expiratory pressure (PEEP) was crucial to optimize lung mechanics. Despite an initial failed extubation, the patient was successfully extubated on day 7 with high-flow nasal cannula support and subsequently transferred to a step-down unit with nasal cannula oxygen therapy. Conclusion: This case underscores the importance of a multidisciplinary approach and dynamic therapy adjustments based on clinical response in managing AHRF in OHS patients with complex comorbidities. Early broad-spectrum antibiotics, careful fluid management, and gradual weaning from mechanical ventilation are critical for successful outcomes.